The Illegal Migration Experiences of Returnees to Omo Nada District, Jimma Zone, Oromia National Regional State, South West Ethiopia (Research, Society and Development, 2019)
Despite the fact that the illegal migration experiences of the returnees are important to design effective programs to reintegrate them into the community, there is scanty of information for the returnees to Omo Nada district.  The purpose of this study is to investigate the physical, economic and social abuse and exploitation faced by the returnees en route and in the place of destination. To this end, in-depth interviews, key informant interviews and focus group discussions were undertaken to collect qualitative data required for the study. The data was transcribed and analyzed thematically.  The results of the findings showed that the migrants were physically exhausted en route with hunger and thirst, subjected to physical abuse such as insults, beating, slapping, kicking, and bodily burn from the smugglers.  Injuries inflicted included bodily wounds, broken limbs and ribs. In addition to the physical abuse, the smugglers and traffickers robbed, and exploited migrants economically charging them for extra services at different transit points. This in turn made the migrants ended in debt bondage. Women became subject to sexual abuse by smugglers and by employers. The abuse continued in the country of destination by employers themselves. Economic exploitation took the form of long working hours with little rest, difficult workloads, reduced pay or wages withheld altogether. Punishment was particularly harsh for those with few or no skills. In addition, the situation deprived the study participants from getting sufficient or healthy food and theircommunication with their families left behind in the home country was restricted.  Women, usually domestic workers, had been subject to sexual abuse by employers and their families.